2012
DOI: 10.4172/2155-9864.1000118
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Audit of Blood Transfusion Reactions in Tertiary Care Hospital for the Use of Blood and Blood Components

Abstract: Aims and Background: Like any other drug, therapeutic use of blood and its components has its own side effects, adverse reactions and risks involved. Overall use of blood has been on the increase in most tertiary care hospitals. Since the guidelines for blood and its components use in a clinical setting are well defined, but not practiced in reality, the present study aims at defining the problems associated with blood transfusion in the light of its risks and benefits as a drug. Materials and Methods:We carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
4
0
1
Order By: Relevance
“…Packed Red Blood Cells were more frequently involved in acute transfusion reactions. These results were correlated with the study done by Rajini Bassi et al [8,13,20].…”
Section: Resultssupporting
confidence: 91%
“…Packed Red Blood Cells were more frequently involved in acute transfusion reactions. These results were correlated with the study done by Rajini Bassi et al [8,13,20].…”
Section: Resultssupporting
confidence: 91%
“…During the study, O positive blood/blood component units was found to be predominant. These observations were found to be similar with the study conducted by Venkatachalapahy TS [6].…”
Section: Discussionsupporting
confidence: 92%
“…In surgery department, transfusions post-surgery was found to be more followed by pre-surgery and intra surgery. This was coinciding with the study carried by Venkatachalapahy TS [6].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations